THE CONCEPT OF AT-TARIQ ILA ALLAH (THE PATH TO ALLAH) ACCORDING TO SHEIKH ZAKARIYYA AL-ANSARI IN THE AL-FUTUHAT AL-ILAHIYYAH MANUSCRIPT. - Syibromalisi, Arif; Akbar, Ali; Kholis, Nurman; Firmanto, Alfan; Kurniawan, Cecep Soleh (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT This article examines an Arabic manuscript, al-Fut???t al-Il?hiyyah, authored by an esteemed Egyptian scholar, Sheikh Zakariyy? al-An??r?. This text encapsulates a summary (mukhta?ar) of Sufi knowledge. The primary aim of this research is to overview of the content of al-Fut???t al-Il?hiyyah and dissect the teachings of Sufism embedded within the text. The research utilizes philology and Sufism theories. Philology aids in the accurate translation of the text, preserving the integrity of the original content while making it accessible to the intended audience. On the other hand, Sufism theories provide a framework to unearth the profound meanings and teachings that the text holds within its narrative. The findings from this analysis reveal that Sheikh Zakariyy? al-An??r?'s work, al-Fut???t al-Il?hiyyah, is characterized by its emphasis on practical or ethical Sufism. The pivotal concept highlighted throughout the text is the “path to Allah” or Maq?m?t. This includes a spectrum of concepts such as Taubat (Repentance), Zuhud (Asceticism), Tawakkal (Reliance on God), 'Uzlah (Seclusion), Zikr (Habitual Remembrance), Tawajjuh il? All?h bi al-Kulliyyah (Total Focus on Allah), ?abr (Patience), Mur?qabah (Spiritual Supervision), and Ri?? (Contentment). Overall, this research underscores the depth and richness of Sufi teachings within al-Fut???t al-Il?hiyyah, and the significant role of such texts in preserving and disseminating these teachings. Keywords: al-Fut???t, al-Il?hiyyah, Maq?m?t, Zakariyy? al-An??r? ABSTRAK Artikel ini mengkaji teks al-Fut???t al-Il?hiyyah (FI) karya seorang ulama Mesir bernama Syaikh Zakariyy? al-An??r? yang berisi ringkasan (mukhtasar) ilmu tasawuf. Tujuan penelitian ini adalah menyajikan tinjauan isi teks al-Fut???t al-Il?hiyyah dan analisis ajaran tasawuf pada teks. Untuk mencapai tujuan tersebut, digunakan teori filologi dan tasawuf. Hasil penelitian ini adalah teks FI karangan Zakariyy? al-An??r? ini mempuyai corak tasawuf amali atau akhlaki, dengan konsep “jalan menuju Allah” nya atau dikenal dengan Maq?m?t, yang meliputi Taubat, Zuhud, Tawakkal, ‘Uzlah (mengasingkan diri), Membiasakan Zikir, Tawajjuh il? All?h bi al-Kulliyyah (totalitas menghadap Allah), Sabar, Mur?qabah (pengawasan Allah), dan Ri??. Kata kunci: al-Fut???t, al-Il?hiyyah, Maq?m?t, Zakariyy? al-An??r?